Emergency Vascular Surgery : A Practical Guide - Wahlberg, Eric; Goldstone, Jerry (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book provides clear, concise guidance on the surgical management of all kinds of emergent vascular problems and focuses in particular on open surgical strategies. The aim is to provide a combined text and hands-on guide that will permit rapid retrieval of information when treating vascular surgical patients in the emergency room. Emergency Vascular Surgery: A Practical Guide is organized into two sections, on specific body areas and general concepts. The first section covers the body from head to toe, with separate chapters for injuries and non-traumatic disease, while the second discusses general principles relating to emergent vascular surgical practice and provides broad vascular surgical guidelines for the inexperienced surgeon. Chapters in the first section are uniformly organized, addressing incidence, etiology, and pathophysiology; clinical presentation; suggestions for workup and diagnosis; and management and treatment. Initial management, selection of patients for emergent surgery, and the performance of common vascular surgical procedures are all carefully explained. The focus on a hands-on approach and practical tips will be invaluable in the clinical setting for both more experienced surgeons and newcomers to the field.